The President's Authority in the Organization of Political Campaign for General Elections May Lead to Presidential Bias - Oktarina, Evi; Mufakkar, Sayyidina (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The issue of whether the president is allowed to campaign is not a new one, as stipulated in Article 299 of Law Number 7 of 2017 concerning General Elections, which states that the President and Vice President have the right to conduct campaigns. This raises concerns about the President potentially favoring one pair of candidates to the advantage or disadvantage of other election participants during the campaign period. The purpose of this research is to examine the impact of the President's authority in conducting election campaigns. This study is juridical-normative (legal research), utilizing a descriptive approach based on secondary data. Article 299 of Law Number 7 of 2017 concerning Elections states that the President has the right to conduct campaigns, while ensuring the continuity of state administration tasks, refraining from using state facilities, and avoiding actions that could benefit or harm any pair of candidates. This situation can lead to presidential bias and tendencies toward favoring one pair of candidates, misuse of authority by exploiting state facilities for non-state interests, and the potential for actions that could influence the electoral prospects of each pair of candidates positively or negatively.